Exploration of the factors of mathematics anxiety and its impact on the achievement of students in mathematics: A systematic review - Kaushal, Rekha; Rose, Shiny Charles; Sehrawat, Sunita; Sharma, Rachna; Lata, Parvesh; Gorakhnath, Igona (International journal of health sciences, 2022)
Mathematics is considered to be an important discipline and every student globally is bound to learn mathematics in curriculum for better opportunities in future and leading a successful life. Basic math skills are important for success in school and everyday life. Yet many people experience uneasiness and fear when dealing with numerical data, often regarded as math anxiety but Math anxiety is not limited to a minority of individuals nor to one country. International comparisons of high school students show that some students in every country are anxious about math. A review of various research papers is presented in this article for exploring the factors of math anxiety among students and how math anxiety has affected the achievement among students in the subject of mathematics.